2018
DOI: 10.1074/jbc.ra118.003557
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a picomolar-affinity, high-specificity antibody targeting phosphorylated tau

Abstract: Antibodies are essential biochemical reagents for detecting protein post-translational modifications (PTMs) in complex samples. However, recent efforts in developing PTMtargeting antibodies have reported frequent nonspecific binding and limited affinity of such antibodies. To address these challenges, we investigated whether directed evolution could be applied to improve the affinity of a high-specificity antibody targeting phospho-threonine 231 (pT231) of the human microtubule-associated protein tau. On the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 76 publications
0
19
1
Order By: Relevance
“…Site-specific phosphorylation of tau is critical in understanding the molecular biology of tau and is a welldefined target in neurodegeneration. The specificity of phospho-tau antibodies is critical for reproducible and sensitive detection (Li et al 2018;Lothrop et al 2013). Phospho-tau antibodies should interact only with the target epitope sequence with site-specific phosphorylation, and not with nonphospho-tau or phospho-tau at off-target sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Site-specific phosphorylation of tau is critical in understanding the molecular biology of tau and is a welldefined target in neurodegeneration. The specificity of phospho-tau antibodies is critical for reproducible and sensitive detection (Li et al 2018;Lothrop et al 2013). Phospho-tau antibodies should interact only with the target epitope sequence with site-specific phosphorylation, and not with nonphospho-tau or phospho-tau at off-target sites.…”
Section: Discussionmentioning
confidence: 99%
“…1a) for its ability to discern phospho-specificity using 3 previously characterized anti-tau antibodies. Tau-5 is a pan-tau antibody that shows phosphorylation-independent binding (LoPresti et al 1995;Carmel et al 1996), 3.24 is a high specificity scFv to pThr231 tau (Li et al 2018), and ab131354 targets pSer262 tau but have shown cross-reactivity to non-phosphorylated tau (Ercan et al 2017). Tau-5 indeed showed binding to both EGFP-tau WT and iRFP-tau WT treated with λ PP (Fig.…”
Section: Phi: a Generalizable Parameter For Measuring The Specificitymentioning
confidence: 94%
See 1 more Smart Citation
“…1b ) [ 32 ]. The fact that these antibodies were raised using phosphorylated peptides as antigens illustrates the importance of performing negative selections to remove nonselective binders during the antibody screening process [ 33 , 34 ]. The structural analyses revealed that the antibodies engage the phosphate group using diverse complementarity determining region (CDR) residues including those in CDR H1, H2, H3, or L1 ( Fig.…”
Section: Insights From Structural Analysis and Engineering Of Antibodies Targeting Phosphorylated Taumentioning
confidence: 99%
“…It is important to note that fine-tuning scFV to harbor high or low binding affinity is an important avenue for improving CAR-T cells in providing safer and better anti-tumor effect. Various protein engineering approaches such as directed evolution [84] , domain exchange [85] , coupled with high-throughput analysis using phage display [88] can assist in scFv fine tuning.…”
Section: Car-t Cells Infiltrating the Tumor Microenvironment (Tme)mentioning
confidence: 99%